Relationship between level of adherence with antihypertensive medication use and quality of life of hypertensive patients at Umbulharjo II community health center - Padmasari, Siwi; Laim, Lidya Adriana Clarita; Setiawati, Margarita Krishna (MEDIA ILMU KESEHATAN, 2024)
Background: Hypertension is one of the most common non-communicable diseases in Indonesia. Compliance with the use of antihypertensive medications is a major factor in the implementation of hypertension, which can affect a hypertensive patient's quality of lifeObjective: The aim of this study is to find out the relationship between compliance with antihypertensive drug use and the quality of life of hypertensive patients in Puskesmas Umbulharjo II.Methods: The study uses a cross-sectional analytical observational design with data collection on compliance level with MMAS-8 questionnaires and quality of life with the SF-36 questionnaire. The sampling technique purposively sampled 202 patients. Data analysis was done with the Spearman test.Results: The results of the study showed that the majority of patients aged >60 years (67.33%), female sex (65.84%), last high school education (42.08%), work as a householder (45.54%), have concomitant diseases (72.28%), suffer from hypertension for 1–5 years (43.77%), receive single therapy (92.57%), and the most frequently used type of antihypertensive drug is amlodipine (90.10%). The rate of compliance with the use of antihypertensive drugs is in the moderate category (37.62%), and the quality of life is in the high category (73.76%).Conclusion: There is a relationship between the level of compliance with antihypertensive medication use and the quality of life of hypertensive patients in Puskesmas Umbulharjo II (p-value=0,001).